Molecular Detection of Bacterial Pathogens Directly from the Nasal Swabs and Lung Tissue of Sheep and Goats - Thakur, Sunaina; Verma, Subhash; Dhar, Prasenjit; Sharma, Mandeep (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Respiratory infections of sheep and goats cause heavy morbidity and mortality, leading to huge economic losses. Conventional methods of diagnosis that include isolation and identification of incriminating microbes are time-consuming and fraught with logistic challenges. Direct detection of incriminating microbes using molecular tools is gaining popularity in clinical, microbiological settings. In this study, a total of 50 samples (44 nasal swabs and 6 lung tissues) from sheep and goats were screened for the detection of different bacterial species by in vitro amplification of genus or species-specific genes. Histophilus somni was detected in 2% goat samples, Trueperella pyogenes in 20% goat nasal swabs, whereas 22% goat nasal swab samples were found positive for Mycoplasma spp. None of the samples from sheep was detected positive for H. somni, T. pyogenes, Mycoplasma spp. Similarly, all samples, irrespective, whether from sheep or goats, showed negative results for Pasteurella multocida, Mannheimia haemolytica, and Corynebacterium pseudotuberculosis.